Are there differences among anti-TNFa biological drugs? - G. Valesini (PAGEPress Publications, 2011)
Objective: To provide an analysis and a guide tool in using TNFa-antagonists in the current clinical practice. Methods: Review of the literature on the differences among the three TNFa-antagonists in terms of molecular structure, mechanism of action, pharmacokinetics, effects on the immune and neuroendocrine systems, and therapeutic indications. Results and conclusions: Unfortunately, results of direct comparison studies are lacking. One could obviate this problem by performing statistical-mathematical extrapolations, but there are very few and very small-sized published experimental evidences.